Dualisme Kewenangan Pengadilan Negeri dan Pengadilan Agama dalam Pengangkatan Anak Beragama Islam - Dian Prameswari, Ineke; Rosmidah, Rosmidah; Oktaviarni, Firya (Zaaken: Journal of Civil and Business Law, 2025)
This study aims to analyze judicial authority in cases of child adoption for Muslims, particularly the conflict between the jurisdiction of the District Court and the Religious Court. Child adoption plays an important role in ensuring the protection and welfare of children, yet in practice it often creates dualism of authority that leads to legal uncertainty. This research applies a normative juridical method with statutory, conceptual, and case study approaches. The findings reveal that District Courts continue to accept and adjudicate adoption cases involving Muslim children based on the Child Protection Law and Supreme Court Circular Letters. However, this practice contradicts Law Number 3 of 2006 on Religious Courts, which explicitly grants absolute authority over adoption cases for Muslims to the Religious Court. This situation results in a normative conflict between general civil law and Islamic family law jurisdiction. Therefore, harmonization of regulations, clearer delineation of judicial authority, and increased judicial awareness are needed to avoid overlapping decisions. The study concludes that legal certainty and optimal child protection can only be achieved if the absolute jurisdiction of the Religious Court is upheld, in line with the principle of lex specialis derogat legi generali.